Implementation of Individual Counseling for Improving Understanding of Early Marriage Impact for Simarlelan Village Community in South Tapanuli, North Sumatera Indonesia - Senida Harefa (Conference Series, 2020)
This study aims to improve understanding of the impact of early marriage for young mothers in the village of Simarlelan through the implementation of individual counseling, using descriptive qualitative research methods and a total of 15 research sample. Data was gathered by closed questionnaire and interview upon the sample. The results showed that individual counseling can increase the understanding of the impact of early marriage for young mothers which was proved by changes in attitudes and behavior towards their commitment to choose school rather than marrying their children at an early age, and an increasing in knowledge of managing and caring the household (child and husband) is better.